Technical Efficiency Analysis at BUKU 1 Banks in Indonesia Using the Data Envelopment Analysis (DEA) Method Period 2016 – 2017 - Kuncoro Budi Satrio; Erric Wijaya (Jurnal Ilmu Manajemen & Ekonomika, 2020)
This study began with an observation of the financial performance of banks in assessing the efficiency of commercial banks in Indonesia in the 2016 period and found inefficiency problems in BUKU I banks based on efficiency values (BOPO) as an indicator of bank efficiency. This study is an analysis of the measurement of bank efficiency values using quantitative analysis with secondary data obtained from the balance sheet and income statement for each bank sample (DMU) for the period 2016 - 2017 using a math-ematical model (linear program) with the Non-Parametric Data Envelopment Analysis (DEA) measure-ment method oriented to Input and assume Variable Return to Scale (VRS) with a sample of 17 Bank sam-ple data during the period 2016-2017. In each DMU there are two variables namely input and output, where the input variable consists of Price of Labor (X1), Price of Fund (X2) and Price of Physical Capital (X3) while the output variable consists of Credit (Y1), Interest Income (Y2) and other Operating Income (Y3). From the results of the measurement of efficiency using the DEA method of the 17 bank samples there are 6 efficient banks while 11 other banks are inefficient. The DEA method measurement results also get an inefficient output variable projection value, from 34 inefficiencies of output variables found there are 4 inefficiencies in the given credit variable, 15 inefficiencies in the Interest Income variable and finally 15 inefficiencies in other Operating Income variables. From the measurement of the efficiency value using the DEA method, the Bank's efficiency and inefficiency values are obtained and the factors causing the Bank's inefficiency so that these factors can be used as material for the Bank's evaluation in improving the Bank's strategic planning .